Phage‐Host Interactions in Flavobacterium Pathogens and the Potential of Phage‐Based Disease Control in Salmonid Aquaculture - Lotta A. I. Landor; Valeria Ruffo; Lotta‐Riina Sundberg; Lone Madsen; Mathias Middelboe (Reviews in Aquaculture, 2026)
A major bottleneck to the projected expansion of the aquaculture industry is disease outbreaks caused by bacterial pathogens. Fish diseases caused by Flavobacterium pathogens are persistent in salmonid aquaculture, and treatment is limited to antimicrobials, which contaminate the aquatic environment and promote antimicrobial resistance. Bacteriophages (phages) are viruses that naturally kill bacteria, and Flavobacterium ‐infecting phages have shown promise in preventing and controlling disease and biofilm formation in aquaculture. This review compiles current knowledge on Flavobacterium ‐phage interactions and applications. We outline the diversity and distribution of Flavobacterium hosts and phages, and discuss the connection between the type IX secretion system, the gliding motility machinery, phage susceptibility, and host virulence. While there is still much to learn about phage resistance mechanisms, the frequent observation that phage resistance is associated with loss of pathogen virulence points to phages as a promising avenue for future pathogen control. Phages infecting Flavobacterium hosts also show persistence to environmental and storage conditions, making them potentially suitable for the development of phage products. Finally, we assess the remaining challenges concerning regulation of phage products, manufacturing at scale, as well as unresolved research questions that need to be addressed to supply the aquaculture industry with alternative treatment and prevention methods in the future.

Revealing the mechanism of Burkholderia sp. Pyr-1 driven removal of pyraclostrobin-contamination through soil microbial community function and assembly - Hongming Liu; Siwen Wang; Zhengqi Zhang; Xiang Li; Yujie Ren; Yuanxiu Wang; Junwei Huang; Lina Sun (Applied Soil Ecology, 2025)

New wine in old bottles: Modification of the Na + /K + ‐ ATPase enzyme activity assay and its application in salmonid aquaculture - Marius Takvam; Kristina Sundell; Henrik Sundh; Naouel Gharbi; Harald Kryvi; Tom Ole Nilsen (Reviews in Aquaculture, 2024)
The Na + , K + ATPase (NKA) enzyme is important to generate the transmembrane ion gradient in the gills, intestine, and kidneys, hence, is vital for secondary transport of fluids and different solutes in teleosts. Gill NKA enzyme activity is often used as a proxy for parr–smolt transformation (PST) during which anadromous salmonids prepare for seawater (SW). Increased intensification and production of larger smolts in modern salmonid aquaculture has resulted in reports of gill NKA activity being less reliable as a proxy for smolt quality. Consequently, changes in mRNA nka ‐ α1b / α1a ratios in gills are increasingly used as indicators of PST. However, nka isoform mRNA abundance may not reflect translation into the functional protein, nor the activity of the mature enzyme. This may limit the predictive power of molecular markers under certain environmental conditions, rearing regimes and biological scenarios. During PST, the osmoregulatory transformations necessary for SW tolerance and survival does not only occur in the gills. Equally important are the changes in ion transporting activities, including NKA activity, in the intestine and kidneys. However, to our knowledge, there are no previous studies addressing the timing and concurrent changes in NKA activity in the three osmoregulatory tissue during PST. Here we present modifications and optimization of the NKA enzyme activity protocols for gill, intestinal and kidney tissue and outline how to best utilize NKA activity measurements as part of a more holistic approach to evaluate overall smolt quality in modern aquaculture.

Response of tidal creek networks and tidal connectivity to coastal squeeze of saltmarshes in the southern Bohai Bay - Xuezhong Fan; Huamei Huang; Qinglong Zhang; Na Sun; Yangang Wang (New Zealand Journal of Marine and Freshwater Research, 2022)
Coastal squeeze of saltmarshes (CSS) has substantially eliminated valuable intertidal habitats and worsened local tidal hydrological environment by disintegrating tidal creek networks and losing tidal connectivity (TC). In this study, we explored the process response of creek network structure and TC to CSS dynamics, taking the southern Bohai Bay of China as a case study area. With the Landsat series data and ArcGIS spatial analysis, the morphological and structural evolution of tidal creek systems were quantified by four parameters: creek order, creek length, creek branch point, and network catchment area. Also, the TC was assessed and visualised based on a geostatistical connectivity method. It was found that low‐order small creeks were more sensitive and vulnerable to CSS and the creek network would face disintegration when about 50% of the saltmarsh squeeze degree occurred, which has been observed as a crucial threshold. In the seaward direction, the CSS process has led to the continuous replacement of high TC areas by low TC areas, greatly altering the original natural TC pattern. Revealing the relationship between CSS and creek network structure and TC will allow a further understanding of the degradation of intertidal ecosystems, and will promote their ecological and hydrological restoration.

Attraction and repulsion of mobile wild organisms to finfish and shellfish aquaculture: a review - Myriam D. Callier; Carrie J. Byron; David A. Bengtson; Peter J. Cranford; Stephen F. Cross; Ulfert Focken; Henrice M. Jansen; Pauline Kamermans; Anders Kiessling; Thomas Landry; Francis O'Beirn; Erik Petersson; et al. (Reviews in Aquaculture, 2018)
Knowledge of aquaculture–environment interactions is essential for the development of a sustainable aquaculture industry and efficient marine spatial planning. The effects of fish and shellfish farming on sessile wild populations, particularly infauna, have been studied intensively. Mobile fauna, including crustaceans, fish, birds and marine mammals, also interact with aquaculture operations, but the interactions are more complex and these animals may be attracted to (attraction) or show an aversion to (repulsion) farm operations with various degrees of effects. This review outlines the main mechanisms and effects of attraction and repulsion of wild animals to/from marine finfish cage and bivalve aquaculture, with a focus on effects on fisheries‐related species. Effects considered in this review include those related to the provision of physical structure (farm infrastructure acting as fish aggregating devices ( FAD s) or artificial reefs ( AR s), the provision of food (e.g. farmed animals, waste feed and faeces, fouling organisms associated with farm structures) and some farm activities (e.g. boating, cleaning). The reviews show that the distribution of mobile organisms associated with farming structures varies over various spatial (vertical and horizontal) and temporal scales (season, feeding time, day/night period). Attraction/repulsion mechanisms have a variety of direct and indirect effects on wild organisms at the level of individuals and populations and may have implication for the management of fisheries species and the ecosystem in the context of marine spatial planning. This review revealed considerable uncertainties regarding the long‐term and ecosystem‐wide consequences of these interactions. The use of modelling may help better understand consequences, but long‐term studies are necessary to better elucidate effects.

Comparative study of the genotoxic response of freshwater mussels Unio tumidus and Unio pictorum to environmental stress - Branka Vuković-Gačić; Stoimir Kolarević; Karolina Sunjog; Jelena Tomović; Jelena Knežević-Vukčević; Momir Paunović; Zoran Gačić (Hydrobiologia, 2014)